Efectos de la acidosis en la sobrevida y funcionalidad de progenitores endoteliales - Mena, Hebe Agustina (2018)
Acidosis is present in the ischemic inflammatory microenvironment, where the formation of new vessels occurs actively. Considering that endothelial colony forming cells (ECFC) have a key role in vasculogenesis, we aimed to investigate the effect of acidosis on the survival and functionality of these endothelial progenitor cells. We demonstrated that the exposure of CFCE to an acid medium (pH 6.6) for 6 hours, followed by the restoration of pH to normal values (7.4), a procedure known as acidic preconditioning, induced a more efficient ex vivo expansion and increased angiogenic activity, since it increased proliferation, chemotaxis, adhesion, tubulogenesis and regenerative potential in vivo, in a murine model of lower limb ischemia. Acidosis increased proliferation by activation of ERK1/2 and AKT and tubulogenesis by p38 inhibition. In addition, acid preconditioning protected from death and increased the ECFC angiogenic responses under inflammatory and high glucose conditions. In conclusion, acid preconditioning represents an effective strategy to optimize ex vivo expansion of CFCE, which are more resistant to adverse conditions such as inflammation and high glucose and with greater therapeutic potential.